Use of Marble Powder and Tile Powder as Cementitious Materials in Concrete - Bheel, N.; Kalhoro, K. A.; Memon, T. A.; Lashari, Z. U. Z.; Soomro, M. A.; Memon, U. A. (Engineering, Technology & Applied Science Research, 2020)
The use of agricultural and industrial waste products as raw materials in the construction industry is investigated extensively. These products are inexpensive and help in environmental sustainability, as environmental pollution is thus reduced. This study focused in investigating the properties of fresh, physical and hardened concrete blended with marble (MP) and tile powder (TP) of several proportions, such as 0%, 5% (2.5%MP + 2.5%TP), 10% (5%MP + 5%TP), 15% (7.5%MP + 7.5%TP), and 20% (10%MP + 10%TP) by weight. A total of 60 concrete cylinders were cast with 0.45 water/cement ratio, 1:1.96:2.14 mix ratio, and were cured for 7 and 28 days. These cylinders were used for checking the compressive and splitting tensile strength of concrete. The experimental results showed that compressive and splitting tensile strengths were increased by 8.90% and 8.30% respectively for the 2.5%MP + 2.5%TP sample after 28 days.